PENGARUH PROFITABILITAS, RASIO NILAI PASAR DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM - Ferdie Hansel Budianto; Rosmita Rasyid (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This study's goal is to examine the impact of profitability, market value ratio, and firm size on stock prices ininfrastructure companies listed on the Indonesia Stock Exchange (IDX). The population for this study is from the period 2019 – 2021 using 186 data which consists of 62 infrastructure companies. Multiple linear regression analysis was employed in this study's data analysis to evaluate the hypothesis, and the research's data processing tools included SPSS Version 25 and Microsoft Excel 2013. The results of this study indicate that profitability has a significant and positive effect on stock prices. While the market value ratio does not have a significant and positive effect on stock prices. And firm size has a significant and positive effect on stock prices.